Impact of Human Papillomavirus-Related Lesions on Quality of Life: A Multicenter Hospital-Based Study of Women in Mainland China. Issue 1 (1st January 2011) - Wang, Shao-Ming; Shi, Ju-Fang; Kang, Dian-Ju; Song, Philip; Qiao, You-Lin
Abstract : Introduction: To date, few studies using a human papillomavirus (HPV)-specific questionnaire have focused on the impact of quality of life (QoL) among women with HPV-related lesions in developing countries. Methods: A multicenter, hospital-based survey was conducted from 2007 to 2008. Women 18 to 65 years old who had HPV-related lesions or underwent HPV-related screening interventions during the past 3 months were recruited and divided into 6 groups based on different diagnoses: (1) normal Papanicolaou (Pap) test result, (2) abnormal Pap test result without HPV test, (3) external genital warts (GWs), (4) precancerous cervical lesions (confirmed by histological diagnoses), (5) HPV positive (HPV+) after abnormal Pap test result, and (6) HPV negative (HPV−) after abnormal Pap test result. Psychosocial burdens were assessed by the HPV impact profile (HIP). The HIP contains 7 domains and 29 questions, and its scores reversely relates to the subjects' QoL. Results: A total of 2605 eligible women were enrolled. Women with GWs had the highest mean HIP scores (52.2), followed by the group with precancerous cervical lesions (48.6), HPV+ after abnormal Pap (45.8), abnormal Pap test result without HPV test (44.1), HPV− after abnormal Pap (43.1), and women with normal Pap endured the least (33.1). "Sexual impact, " "self-image, " and "control/life impact" were the 3 QoL-related domains that affected women the most. The psychosocial burden of urban residents was heavier than that of rural women. Conclusions: Women with GWs and precancerous cervical lesions had the worst psychological burden, and sexual-related concern was the primary cause of burdens regarding HPV-related diseases for Chinese women. In addition to basic medical treatments, psychosocial support systems should be established, and consultation services should be generalized to help alleviate these burdens.